Analisis Tantangan dan Hambatan Penerapan Kurikulum 2013 di MI Ma’arif Budiluhur Kertek - Hasanah, Dwi Umul; Khasanah, Miladina Nur; Hanifah, Desty Putri (Faculty of Teacher Training and Education of Undaris, 2023)
This study aims to analyze the challenges and obstacles in the implementation of the 2013 curriculum, which has been implemented in MI Ma'arif Budiluhur Kertek for 10 years. The results of this study can be used as a guide in determining improvement plans so that the quality of the school is guaranteed. This research is included in the descriptive quantitative research. The research was conducted in MI Ma'arif Budiluhur Kertek with research subject being MI Ma'arif Budiluhur Kertek teacher. The sampling technique was saturated sampling such that all teachers at MI Ma'arif Budiluhur were involved in collecting research data. The instruments used include interview guides, observation sheets, and questionnaires. The research results showed that the problems that arose in the implementation of the 2013 curriculum at MI Ma'arif Budiluhur were related to classroom conditions, too many students, non-linear teacher competency, and a busy school calendar. On the other hand, teachers' difficulties in integrating materials, teachers' lack of IT skills, late distribution of handbooks, and teachers' demands to produce their own learning media are obstacles to the implementation of the 2013 curriculum at MI Ma'arif Budiluhur. This raises challenges to be solved by MI Ma'arif Budiluhur, namely related to teachers' ability and willingness to use technology and mastering 2013 curriculum material.Keywords: 2013 curriculum, challenges, barriers, MI Ma'arif Budiluhur